Evaluasi penerapan standardisasi SNI 8371:2018 dan SNI 8372:2018 pada UMKM Deean Cakes and Bakery - Andriyansa, Padli; Restuasih, Sinta; Gustany, Eko Widodo; Haryudiniarti, Ayu Nurul; Ekardi, Mohammad Luthfi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
MSMEs need implementation of standardization to ensure quality and customer confidence in they products. The implementation of SNI 8371:2018 for Sweet Bread and SNI 8372:2018 for Fresh Bread at Deean Cakes And Bakery MSMEs aims to ensure that every product they produce meets the food safety, health and quality standards set by the government. The Gap Analysis method at is carried out with the aim of identifying things that are still not in accordance with SNI standards, which will later become the basis for preparing quality system documents. The results are several things that still need to be brought in line with SNI standards, such as the absence of a special room for storing goods, the ceiling is still made of plywood which is easily damaged, and some production documentation. MSMEs is implementing a food safety quality management system based on the HACCP (Hazards and Critical Control Points) system.